Analisis Pemanfaatan Sumber Belajar Berbasis Lingkungan dalam Pembelajaran Tematik terhadap Pemahaman Siswa Kelas IV Sekolah Dasar - Puspita, Intan Ecky; Sugiyono, Sugiyono; Erviana, Lina (PGSD STKIP PGRI Pacitan, 2022)
The research aimed to describe: (1) the thematic learning process using environmental-based learning resources; (2) the results obtained from the use of environmental-based learning resources in thematic learning. This research was a qualitative descriptive study. The data collection techniques used were observation, interviews, tests, and documentation. The research location was in SD Negeri 1 Kayen with the subject of class IV students with a total of 13 students. The results of data analysis showed that the thematic learning process for theme 9 sub-theme 1 learning 3 was carried out through three stages, namely; a) in the preliminary stage the researcher conducts orientation in the classroom and continues learning in the yard of the school; b) the core stage of the researcher prepares pictorial media and distributes it to several points in the school environment then students are directed to look for the illustrated media in groups. After that, students return to the meeting point and prepare to present their findings regarding the energy sources found in the school environment; and c) the closing stage, researchers provide tests to measure students' abilities after carrying out the learning process by utilizing environmental-based learning resources. The results of thematic learning in grade IV SD Negeri 1 Kayen students have a better understanding. This can be seen from the test results that exceeded the school's KKM score of 70. The tests carried out obtained an average score of 83.4 with the lowest score of 77.5 and the highest score of 90.